Sistem Pendukung Keputusan Pemilihan Pegawai Non-PNS Terbaik di Dinas Pengendalian Penduduk Dan Keluarga Berencana Kota Binjai Menggunakan Metode Moosra Dan Roc - Rianty Zabitha Siregar; Relita Buaton; Rusmin Saragih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Employee evaluations within an organization are efforts to measure and motivate employees to enhance their skills and abilities. These evaluations are expected to help the organization assess and identify improvements or developments in employee capabilities to support the organization in achieving its goals. The evaluations are anticipated to produce fair and transparent results that are acceptable to all parties involved. The rapid advancement of information technology has brought changes to the employee evaluation process. Specifically, the Population Control and Family Planning Office of Binjai City requires a system that can assist in evaluating the performance of its non-permanent employees. There are various methods that can be used in designing a system to produce the best decisions. Among them is the MOOSRA (Multi-Objective Optimization on the Basis of Simple Ratio Analysis) method, which is one of the multi-objective optimization techniques used in decision support systems. The MOOSRA method is similar to the MOORA method but differs in performance score determination: MOORA uses a reduction operator, while MOOSRA relies on calculations based on criteria and alternative division operators. MOOSRA performs calculations based on the provided criteria and alternatives. To determine the weight of each criterion, the ROC (Rank Order Centroid) method is employed, which assigns weights to each criterion based on their ranking and priority levels. This ensures that the evaluation of non-permanent employees at the Population Control and Family Planning Office of Binjai City produces the best results. The MOOSRA and ROC methods can be used to build a decision support system that delivers optimal evaluations of non-permanent employees. Awarding the title of